The psychosocial impact on single mothers' well-being - A literature review - M. K. Dharani; J. Balamurugan (Wolters Kluwer Medknow Publications, 2024)
In India, single-parent families are proliferating. In particular, women are taking the lead in assuming the role. They are the most vulnerable of all the disadvantaged groups. Due to an absence of financial and social support, single mothers endure a great deal of emotional strain. So, the aim of the study is to investigate the various psychosocial factors that influence the well-being of single mothers. Additionally, this research seeks to assess the coping strategies employed by single mothers. This article reviews 80 studies on psychosocial concerns faced by single mothers, focusing on mental health, challenges, and social support. It cites 71 publications from 80 sources from Google Scholar, Scopus, Web of Science, and PubMed, between 1980 and 2023. The study used keywords as a search strategy such as "single mother," "mental health," "challenges," and "social support." The results showed that the absence of financial resources, education, and social support had a negative impact on the emotional and social well-being of single mothers. Children of single mothers are more likely to struggle with addictions like alcoholism, tobacco use, delinquency, hazardous sexual behavior, and even suicidal thoughts due to dysfunctional parenting. As a result, single mothers use their religious convictions, support networks, and social networks as coping mechanisms. The study implies that premarital counseling and health education are essential for young couples to prevent family disintegration in the event of divorce and separation. To provide assistance and improve the overall quality of life for this vulnerable population, collaboration between government and nongovernment organizations is necessary.